Assessment of Middle School Mathematics Educators' Grasp, Comprehension, and Utilization of Ethnomathematics in Conducting Math Instructional Sessions - Sari Suswati; Kanya Lailatul Ulya; Atikah Rakhmawati (Global Education : International Journal of Educational Sciences and Languages, 2024)
This research evaluates the understanding and application of ethnomathematics by junior high school level mathematics educators in carrying out mathematics learning sessions. The focus of this research is to identify the extent to which these teachers understand ethnomathematics concepts and how effective they are in integrating them into mathematics learning activities. Through this analysis, we can evaluate the impact of teachers' ethnomathematics understanding on students' mathematics learning experiences at the junior high school level.